Vibration-based tension estimation of short helically multi-stranded wires under low axial tension. (15th January 2023) - Do, Hyun-Dong; Park, Kyoung-Su
Highlights: Existing tension estimates for short cables under low axial tension were unavailable. A short helically stranded wire's tension under low axial tension was linear rather than quadratic in relation to C/f . Under low axial tension, a practical vibration-based tension estimation method was developed for the short helically stranded wire. Experimental data were used to validate the vibration-based tension estimation method. Abstract: When cables are used to support systems, accurate tension monitoring is critical. However, almost all existing tension estimation models are inaccurate for short cable under low tension. Short helically stranded wire cables under low axial tension are widely used especially in cable-driven robots (CDRs). A vibration-based equation accurately to evaluate applied tensions for short helically stranded wires under low axial tension was developed. We employed two kinds of short cables with diameters of 2.4 and 3.2 mm under tensions of approximately 20 to 110 N. There were no known tension estimates for these conditions up to now. We used a best-fit numerical approach (employing the measured first frequencies and C / f 1 values) to derive an accurate equation. The helically stranded wire theory was also used to validate the feature. Finally, we verified experimentally the derived equation using different material and different diameters and the estimates agreed with the experimental data well.